Hubungan Konsentrasi PM 2,5 dengan Keluhan Gangguan Pernapasan pada Pekerja Uji Mekanis UP PKB Pulo Gadung - Tampubolon, Armando Wijaya; Ramdhan, Doni Hikmat Hikmat (National Journal of Occupational Health and Safety, 2025)
Vehicle emissions including traffic and transportation emissions have become the largest source of particulates in many cities in various countries. Health problems due to particulates from motor vehicles can not only occur around the highway, but can also occur in industries that are in contact with motor vehicles. Under these conditions, researchers wanted to conduct a study at UP PKB Pulo Gadung to see the relationship between PM2.5 concentrations and complaints of respiratory problems. The study sample totaled 38 people, consisting of mechanical testers and FKM UI community members as a comparison sample. The average result of measurements taken in the mechanical test track was 100.53 μg/m3. While the measurement results in the FKM UI environment as a comparison averaged 56.72 μg/m3. A total of 33 out of 38 samples experienced respiratory symptoms, with the most experienced symptom being sneezing (76.31%). From the results of the chi-square test between PM2.5 concentrations and respiratory complaints, the p-value = 0.05 was obtained, which means that there is a significant relationship between PM2.5 concentrations and respiratory complaints. Keywords: PM2.5, respiratory symptoms, motor vehicle emissions.